Drivers of abundance and spatial distribution in Southern Ocean peracarid crustacea. (September 2021) - Di Franco, Davide; Linse, Katrin; Griffiths, Huw J.; Brandt, Angelika
Highlights: Depth drives peracarid assemblage structure at wide geographical scale and bathymetric range. Peracarid assemblage structure from the shelf and that from the deep sea are dissimilar. The correlation between depth and peracarid abundance differs depending on the peracarid order. Abstract: The Southern Ocean (SO) continental shelf and deep sea are environments characterised by different benthic communities. Their structure and composition are driven and shaped by different variables: whilst on the continental shelf physical environmental variables are the main drivers shaping faunal abundance, structure and composition, the deep-sea fauna is most problably driven by biological variables such as predation and competition. Among shelf and deep-sea benthic communities, peracarids (e.g. amphipods and isopods) are one of the most dominant groups, showing high levels of abundance and diversity in both environments. Knowledge on their assemblage structure and composition in the SO remains limited, as well as the knowledge of the environmental variables that influence them. Therefore, the aim of our study was to investigate peracarid assemblages from the SO continental shelf and deep sea and to assess the main drivers shaping their assemblage structure along a wide bathymetric gradient (from 160 m to about 6000 m depth) and at a large geographic scale. We analysed the spatial distribution of 183, 606 peracarids sampled using an epibenthic sledge (EBS) during nine different expeditions in the SO, covering a latitudinal range of 77° to 41° South. Depth was identified as the main driver shaping peracarid abundance pattern, their assemblage structure from the continental shelf (<1499 m) was dissimilar to that from the deep sea (>1500 m). Also, depth was differently correlated with different peracarid orders: while isopod abundances increased with depth, amphipods and mysids were negatively correlated; no correlation was found with cumaceans and tanaidaceans. The dissimilar peracarid assemblage structure between the SO continental shelf and the SO deep sea can be due to the assumption that there are different driving forces shaping benthic assemblages from these two environments (physical variables on the continental shelf, biological interactions in the deep sea). As a result, we also suggest that environmental changes due to climate change (e.g. temperature, ice coverage, productivity) would have different consequences depending on the bathymetric range considered.